Lexicon-based Sentiment Analysis for Product Design and Development - Sutrilastyo, Sutrilastyo; Diar Astanti , Ririn (Universitas Atma Jaya Yogyakarta, 2021)
This paper discusses the role of text mining and sentiment analysis in collecting and analyzing customers’ verbatim/voice of the customer for product design and development. In the illustration case of designing car underbody, the data were collected from a car online forum discussion website and processed using text mining techniques with “underbody” as a keyword. The result of the analysis finds there are worries regarding underbody durability against rust and damages. This finding is used as a reference point for the car underbody design process.